Polymer action on alkali–silica reaction in cement mortar - Feiteira , J. (2012)
Due to the improvement of several properties, such as lower water absorption and increasing resistance to microcracking, polymer modification of mortar and concrete potentially leads to an inhibiting effect on alkali– silica reaction (ASR). In this study, polymer–cement mortars (PCMs) were subjected to accelerated alkali reactivity tests and their performance compared to that of an unmodified cement mortar (CM). Expansion of PCMs was overall higher, but SEM observations revealed apparent lower microcracking intensity of the cement paste, compared to the unmodified CM. Subsequent stiffness damage tests (SDTs) quantified the existing damage after alkali reactivity tests and confirmed the lower microcracking intensity in PCMs.